Pelatihan Penerapan Online dan Blended Learning pada Masa Pandemi Covid-19 di Pondok Pesantren Arrahman Kabupaten Lombok Tengah - Dedi Sumarsono; Taufik Suadiyatno; Muliani Muliani; Moh. Arsyad Arrafii; Abdul Kadir Bagis (Jurnal Pengabdian UNDIKMA, 2021)
This community service was aimed at training the teacher to be familiar with the usage of learning approach that can be applied in the time of covid-19. The training was conducted at Pondok Pesantren Arrahman attended by teachers of Madrasah Tsanawiyah, Aliyah, and SMK Darul Kamilin Bakan. To reach the goal of the program, the material and the application about the learning approach in detail for both online learning and blended learning was delivered to the participants. At the end of the program, evaluation was conducted by giving evaluation sheet to the participants to know whether or not the target of program is achieved. The response of the audience reveals that the program gave some good advantages for the participants as they have new knowledge about the learning approach applied in the time of covid-19. The participants also expected that the same program is conducted in the near future.